1992
DOI: 10.1002/ajim.4700210410
|View full text |Cite
|
Sign up to set email alerts
|

Lung function and precipitating antibodies in low exposed wood trimmers in Sweden

Abstract: Wood trimmers are exposed to molds that periodically grow on timber that may induce alveolitis and obstructive lung disease. We have evaluated respiratory symptoms, bronchial reactivity, and lung function in 28 wood trimmers at a Swedish sawmill and in 19 unexposed office workers. Eleven (sero-positive) of the wood trimmers had precipitating antibodies in peripheral blood against one or several molds. The exposure to dust (median 0.26 mg/m3), viable mold spores (median 2950 cfu/m3), viable bacteria (median 370… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 19 publications
0
28
1
1
Order By: Relevance
“…A significant relationship was found between the reduction in lung function and airborne mold concentrations (Dahlqvist et al 1992). Respiratory symptoms, febrile episodes, allergic diseases such as hypersensitivity pneumonitis, and asthma due to bioaerosol exposure have been documented among workers employed in waste industry (Chiba et al 2009;Poulsen et al 1995).…”
Section: Introductionmentioning
confidence: 91%
“…A significant relationship was found between the reduction in lung function and airborne mold concentrations (Dahlqvist et al 1992). Respiratory symptoms, febrile episodes, allergic diseases such as hypersensitivity pneumonitis, and asthma due to bioaerosol exposure have been documented among workers employed in waste industry (Chiba et al 2009;Poulsen et al 1995).…”
Section: Introductionmentioning
confidence: 91%
“…A temporary decrease in these variables has been reported to be associated with exposure to irritating substances. A decrease in FVC over a shift is, for example, reported to be associated with exposure to diesel engine exhausts (22) and a decrease in FEVI.O over a work week has been reported to be associated with mold exposure in a sawmill (23).…”
Section: Lung Functionmentioning
confidence: 99%
“…Abietic acid and terpene levels were lower than those found in sawmills and joinery shops (Eriksson et al, 1996(Eriksson et al, , 1997Demers et al, 2000) as expected, because sawing tends to rupture wood cells and therefore releases the cell contents, including abietic acid and terpenes. Previous studies in sawmills concluded that wood trimmers exposed to inhalable dust, organic dust (molds), terpenes and endotoxins may develop airway symptoms (Hedenstierna et al, 1983(Hedenstierna et al, , 1986Dahlqvist et al, 1992). Formaldehyde levels were lower than those measured before in plywood mills (Malaka and Kodama, 1990).…”
Section: Discussionmentioning
confidence: 85%